Neonatal Near Miss: the need for a standard definition and appropriate criteria and the rationale for a prospective surveillance system (Clinics, 2015)
In Latin American, there is currently a regional action with the main purposes of putting the concept of severe neonatal morbidity in practice and formulating proposals for interventions. A general overview of neonatal health conditions, including morbidity and mortality, is provided to update regional knowledge on the topic. An example of the development and implementation of the concept of maternal near miss is also provided, followed by results from a systematic review covering all previously published studies on Neonatal Near Miss. Finally, some proposals for building a common concept on the topic and for launching a prospective surveillance study are presented. A Neonatal Near Miss is a neonate who had a severe morbidity (organ dysfunction or failure) but who survived this condition within the first 27 days of life. The pragmatic criteria recommended to be used are as follows: birth weight below 1700 g, Apgar score below 7 at 5 minutes of life and gestational age below 33 weeks. As a proxy for organ dysfunction, the following management criteria are also confirmed: parenteral therapeutic antibiotics; nasal continuous positive airway pressure; any intubation during the first 27 days of life; phototherapy within the first 24 h of life; cardiopulmonary resuscitation; the use of vasoactive drugs, anticonvulsants, surfactants, blood products and steroids for refractory hypoglycemia and any surgical procedure. Although this study starts from a regional perspective, this topic is clearly globally relevant. All nations, especially low and middle-income countries, could benefit from the proposed standardization.